Підсилення залізобетонних конструкцій за допомогою попередньо напружених елементів - Бліхарський, З. Я.; Хміль, Р. Є.; Дудич, С. Б.; Blikharskyy, Z.; Khmil, R.; Dudycz, S. (Видавництво Львівської політехніки, 2018)
Основні конструкції сучасних будівель і споруд виконуються з бетону, залізобетону або цегли. Передчасне руйнування конструкцій, втрата несучої здатності та інших експлуатаційних якостей призводять до небажаних наслідків, і часто несуть загрозу цілісності споруди і навіть життя людей. Тому своєчасне проведення робіт з посилення і ремонту будівельних конструкцій має дуже важливе практичне значення. До теперішнього часу у вітчизняній та зарубіжній практиці накопичено безліч різних способів і конструктивних прийомів посилення. У цій статті описано підсилення конструкцій та експериментальних випробувань залізобетонних конструкцій, підсилених додатково попередньо напруженими елементами під навантаженням. Проаналізовано сучасний стан і тенденції розвитку в галузі переоснащення та реконструкції елементів будівель і споруд. Опрацьовано наукові праці вчених багатьох країн світу в сфері експериментальних досліджень підсилення залізобетонних конструкцій.

The basic design of modern buildings and constructions are made of concrete, reinforced concrete or brick. To date already made significant contributions to science of strengthening of various reinforced concrete structures. As a rule, is insufficient number of instructional materials to strengthen the work of experimental research in this area. Premature destruction of structures, loss of bearing capacity and other operating characteristics can lead to undesirable consequences, and often threaten the integrity of buildings, and even people’s lives. Therefore, the timely implementation of works on strengthening and repair of building structures has a very important practical significance. To date in domestic and foreign practice has accumulated a lot of different ways and constructive methods of amplification. Of which in this article we describe reinforcement of the construction and experimental testing of reinforced concrete structures, reinforced by additional pretensioned elements under load. Analyzes the current state and development trends in the field of re-equipment and reconstruction of elements of buildings and structures. Processed scientific works of scientists of many countries in the field of experimental research of strengthening of concrete structures. Presents a list of scientific works in the field of strengthening of building structures, as well as literature used in writing this work.
Strengthening of reinforced concrete structures using prestressed elements
Keywords: підсилення конструкцій; попередньо напружені елементи; strengthening of structures; prestressed elements; 624.014